Learning Development based on PJBL in Graphic Media Design Report on Alternating Current Circuit Material at SMAN 4 Kejuruan Muda - Ayu Andriani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to create a studet agency through fun learning based on Project Based Learning with PTD Miniature media that can improve scientific skills in Alternating Current Circuit material at the stage of studying state electricity flow to customers and recognizing the functions and benefits of electric energy generation, SUTET in electricity transmission. and distribution of electricity to customers.Observation of the students' complete learning outcomes on average 83.14 and the ability of students in Project Based Learning-based learning process skills with an average of 97.75 and proves that students are actively involved in the learning process.Based on the achievement of the growth of life skills regarding the development of media that is oriented towards meaningfull Learning based on PJBL including; 1) Demonstrating the design of PTD miniature products (Generation, Transmission and Distribution) models of the application of alternating current circuits in daily life and 2) Presenting the results of models of applying alternating current circuits in everyday life in the form of reports and links to upload your information media tubes. This shows that the meaningfull learning developed is successful and can be used to improve students' scientific thinking skills.